Programa de educação pelo trabalho para a saúde/saúde mental: três experiências da Região Metropolitana de Belo Horizonte - Gilsiane Aparecida Ribeiro Braga (2014)
Education in health care is a topic that has attracted many researches. The Ministry of Education and Ministry of Health also have not realized it. There is even an Interministerial Ordinance (nº 2118) 2005 reapproaches these two Ministries, separated in 1953. In 2008 it was created the Education Program for Health at Work (PET-Health), which promotes learning groups in tutorial services of the Unified Health System (SUS). In 2010 a new theme edict was issued: PET-Health/Mental Healfth/crack/alcohol and other drugs (PET/SM). Several projects were selected by Brazil in 2011 to be developed in this Program from the latter edict. In the Metropolitan Region of Belo Horizonte (BH) were selected three projects. This qualitative research is a descriptive case study from a analysis of the three tutorial groups of PET/SM in the Metropolitan Area of Belo Horizonte. The primary objective of this research was to understand how was the process of training in health services in the SUS in PET/SM for students of higher education institutions that participated in the Program in the Metropolitan Region of Belo Horizonte, between April 2011 and March 2012, from the perceptions of the students. The secondary objectives were: 1) discuss, from official documents, the training politics for the SUS in managing of the Lula Government (2003- 2010), focusing on PET-Health; 2) understand what were the obstacles encountered by students to meet the reality of SUS/Mental Health (SUS/SM), comparing the experience of the Program with the curriculum of the courses involved in PET/SM; 3) analyze the introduction of students in the PET/SM, seeking how they saw and noted the Program, still checking that experience impacted in some way in their training. Data collection took place from reading the projects and final reports to the Ministry of Health and interviews with tutors of these projects. Subsequently, interviewed three students of each project, and one student from each tutorial group that has left the Program, but it has remained the same for at least four months. The examination of the material collected was from the content analysis. The author of this research is a psychologist in the City of Betim/MG and there was preceptress students PET/SM in 2011. These students and the tutor of PET/SM from this City were also interviewed. This was one of the aspects that the researcher had to be careful in this work. Thus, authors as Lourau (1993) and Monceau (2008) contributed to the analysis of the implication of the researcher throughout the work of collecting and analyzing data. One of the contributions of this research was to realize that despite the disagreements between managers of education and health and difficulties at certain times of overloaded workers with high demand, the students could participate in the practice areas of municipal services such as SUS and could take advantage of it, taking this unique experience for your professional life.